Promosi Pariwisata Melalui Instagram di Desa Wisata Pelangas Kabupaten Bangka Barat - Hawwa, Kharisma Nur; Sugiman, Sugiman; Peranginangin, Jasanta (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine promotions via Instagram in order to expand the target market and also form brand awareness. This research was carried out using descriptive qualitative research methods through several research stages, namely data collection techniques, data analysis techniques, data validity testing. From these stages it was concluded that Pelangas Tourism Village had an Instagram account but it had not been active since 2022 because they did not remember the email and password for the account and human resources did not understand digital promotions. Based on this, the author created an Instagram account agreed upon with the management with the user name @desawisatakulturjerieng and provided guidance to the management to be able to utilize the features on Instagram in creating content. The formation of branding is also carried out through discussions with the management of the cultural tourism village. In this way, the main theme for posts and hashtags about culture is determined. This is done to increase brand awareness of tourism products in the Pelangas Tourism Village.